“The European Culture is Sinking like Venice”. Italy in Memories of late Jarosław Iwaszkiewicz - Sadoch, Elżbieta (Załącznik Kulturoznawczy, 2024)
The main purpose of this article was to present specific motifs, which occur in the travel reports by an outstanding Polish writer and poet, Jarosław Iwaszkiewicz. As the study showed, Iwaszkiewicz usually mentioned neglected or abandoned places and objects. He was interested in art galleries, churches and chapels with tombstones, cemeteries, old castles and ancient ruins. Moreover, the author of those texts presented famous works of art associated with subjects such as ugliness, suffering and death. He would also write down his own opinions about art and culture. Journeys to Italy contain pessimistic images of the decline of all values, especially of the beauty and goodness. Reading the discussed work, one may get the impression that the writer was visiting not so much the “mythical” Italy, formerly considered a land of wonders and a treasure trove of art, but an entirely different world – one that evokes melancholy, anxiety and a sense of emptiness.